A lithium ion battery positive electrode material and preparation method thereof

By preparing carbon nanotube-covered metal oxides in situ on the surface of the carbon cloth, a carbon nanotube-covered positive electrode material that can be directly used as the positive electrode sheet of lithium-ion battery is prepared, which solves the reduction of specific capacity of existing materials during high current charging and discharging. and the problem of electrode material falling off, high performance and low cost battery material preparation is achieved.

CN115513416BActive Publication Date: 2025-02-21LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211325840.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-02-21
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The specific capacity of the existing lithium-ion battery positive electrode material is significantly reduced during charging and discharging of high current, and requires bonding to the electrode sheet carrier, which has the problem of electrode material falling off, resulting in reduced performance.

Method used

By preparing carbon nanotube-covered metal oxides on the surface of the carbon cloth, and using it as a precursor, the carbon nanotube-covered positive electrode material is prepared, which is directly used as a positive electrode sheet of a lithium-ion battery, avoiding the binder and the use of conductive agents.

Benefits of technology

The high electronic conductivity of the positive electrode material is achieved, and good high-rate charging and discharging performance and cycling performance are shown, with simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115513416B_ABST
    Figure CN115513416B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and discloses a positive electrode material for a lithium-ion battery and a preparation method thereof. The present invention first prepares a carbon nanotube-coated metal oxide in situ on the surface of a carbon cloth, and then uses the metal oxide as a precursor to prepare a carbon cloth-loaded carbon nanotube-coated positive electrode material. The carbon nanotube-coated positive electrode material prepared by the present invention can be directly used as a positive electrode sheet for a lithium-ion battery without coating, and avoids the use of a binder and a conductive agent, so the process is simple and the cost is low. The surface of the positive electrode material particles is uniformly coated with carbon nanotubes, has excellent electronic conductivity, and exhibits good high-rate charge and discharge performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion battery positive electrode materials are an important component of lithium-ion batteries, and their performance is an important factor restricting the capacity of lithium-ion batteries. Lithium-ion battery positive electrode materials include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel cobalt manganese oxide (LiNi a Co b Mn c O2, where a+b+c=1), lithium iron phosphate (LiFePO4), etc. These cathode materials have been commercially applied, but their ionic conductivity and electronic conductivity are low, and the specific capacity will be significantly reduced during high current charging and discharging. In order to improve the conductivity of lithium-ion battery cathode materials, researchers usually modify them by carbon coating.

[0003] For example, patent CN102931397A discloses a method for preparing a carbon-coated modified lithium cobalt oxide positive electrode material, which specifically includes the following steps: (1) adding lithium cobalt oxide to deionized water; (2) adding a soluble organic carbon source accounting for 10% to 30% of the mass of the lithium cobalt oxide to the resulting mixed solution, and then adding a carbonization catalyst accounting for 0.5% to 5% of the mass of the organic carbon source; (3) spraying and granulating the resulting mixed solution through a spray dryer to obtain organic carbon-coated lithium cobalt oxide; (4) charging the obtained lithium cobalt oxide powder into a crucible, heating it to 300°C to 450°C under an inert atmosphere and sintering it for 0.5h to 4h to obtain a carbon-coated lithium cobalt oxide positive electrode material.

[0004] Patent CN108155360A discloses a method for preparing a carbon-coated nickel cobalt manganese oxide positive electrode material. First, Ni x Co y Mn z (OH)2 powder and aniline monomer, dissolve the emulsifier in deionized water, add Ni x Co y Mn z The (OH)2 powder material was stirred and ultrasonically dispersed to obtain solution A; aniline monomer was added to the acid solution and stirred to obtain solution B; solution B was added to solution A, acid was added to adjust the pH of the solution, and magnetic stirring was continued to obtain solution C; an oxidant was added to the acid solution and stirred to obtain solution D; solution D was added dropwise to solution C and stirred, the obtained reaction product was filtered, washed with deionized water and ethanol, and then vacuum dried to obtain polyaniline-coated Ni x Co y Mn z(OH)2 composite material; the composite material powder and the lithium source are mechanically ball-milled on a planetary ball mill and then calcined in an oxygen atmosphere to obtain carbon-coated LiNi after cooling. x Co y Mn z O2 composite positive electrode material.

[0005] However, the above materials all need to be bonded and loaded with the electrode carrier, and cannot generate electrode sheets in situ. During use, the electrode material may fall off, thereby reducing the performance of the lithium-ion battery.

[0006] Therefore, how to prepare an electrode material that can be directly used as a positive electrode and has high electrochemical performance is of great significance to the development of lithium-ion batteries. Summary of the invention

[0007] The object of the present invention is to provide a lithium ion battery positive electrode material and a preparation method thereof, so as to solve the above-mentioned problems existing in the lithium ion battery positive electrode material prepared by the prior art.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0010] (1) Mixing a soluble metal salt, urea, and water to obtain a precursor solution; adding carbon cloth to the precursor solution to perform a hydrothermal reaction to obtain a carbon cloth loaded with metal oxides;

[0011] (2) placing the metal oxide-loaded carbon in a tubular furnace and heating it to a reaction temperature; after reaching the reaction temperature, atomizing the carbon source solution and passing it into the tubular furnace through a carrier gas, so that the carbon source and the metal oxide-loaded carbon cloth react at the reaction temperature; continuously passing the carbon source during the reaction; stopping passing the carbon source at the end of the reaction; and naturally cooling the carbon cloth to obtain the metal-coated carbon cloth loaded with carbon nanotubes;

[0012] (3) subjecting the carbon cloth loaded with carbon nanotubes and coated with metal to an oxidation reaction in an air atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with metal oxide;

[0013] (4) The carbon cloth loaded with carbon nanotubes and coated with metal oxides is mixed with a lithium source solution and subjected to a hydrothermal reaction to obtain a precursor; the precursor is calcined to obtain a positive electrode material for a lithium-ion battery.

[0014] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium-ion battery, the mass volume ratio of the soluble metal salt, urea and water in step (1) is 1-20 g: 1-7 g: 50-80 mL.

[0015] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium-ion battery, the soluble metal salt in step (1) is one or more of cobalt nitrate, ferric nitrate, nickel nitrate, manganese nitrate, cobalt chloride, ferric chloride, nickel chloride, and ammonium vanadate.

[0016] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium-ion battery, the step (1) further comprises immersing the carbon cloth in a precursor solution for 20 to 24 hours before the hydrothermal reaction; the temperature of the hydrothermal reaction is 120 to 130° C.; and the time of the hydrothermal reaction is 6 to 8 hours.

[0017] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium ion battery, the carbon source solution in step (2) is a mixed solution of anhydrous ethanol and water as a carbon source; the carbon source is one or more of glucose, sucrose, water-soluble starch, dextrin, and citric acid; and the mass volume ratio of the mixed solution of soluble metal salt, carbon source, anhydrous ethanol and water is 1-20 g: 5-6 g: 40-60 mL.

[0018] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium ion battery, the carrier gas in step (2) is argon; the flow rate of the carrier gas is 5-50 mL / min; the reaction temperature is 900-1600° C.; and the reaction time at the reaction temperature is 10-120 min.

[0019] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium-ion battery, the temperature of the oxidation reaction in step (3) is 200-500° C.; and the time of the oxidation reaction is 1-5 h.

[0020] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium ion battery, the concentration of the lithium source solution in step (4) is 0.1-0.5 mol / L; the mass volume ratio of the soluble metal salt to the lithium source solution is 1-20 g: 50-100 mL;

[0021] The lithium source solution is an aqueous solution of a lithium source or an aqueous solution of a mixture of a lithium source and a phosphorus source; the lithium source is one or more of lithium chloride, lithium hydroxide, lithium acetate, lithium citrate, and lithium dihydrogen phosphate; the phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid;

[0022] The molar ratio of lithium element to phosphorus element in the aqueous solution of the lithium source and the phosphorus source mixture is 1:1.

[0023] Preferably, in the above-mentioned method for preparing a positive electrode material for a lithium-ion battery, the temperature of the hydrothermal reaction in step (4) is 200-250° C.; the time of the hydrothermal reaction is 2-20 h; the temperature of the calcination is 700-1500° C.; and the time of the calcination is 2-12 h.

[0024] The present invention also provides a lithium ion battery positive electrode material prepared by the above preparation method.

[0025] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention first prepares carbon nanotube-coated metal oxide in situ on the surface of carbon cloth, and then uses the metal oxide as a precursor to prepare a carbon cloth-loaded carbon nanotube-coated positive electrode material. The carbon nanotube-coated positive electrode material prepared by the present invention can be directly used as a positive electrode sheet of a lithium ion battery without coating, and avoids the use of a binder and a conductive agent, so the process is simple and the cost is low. The surface of the positive electrode material particles is uniformly coated with carbon nanotubes, has excellent electronic conductivity, and exhibits good high-rate charge and discharge performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0028] Figure 1 The process flow chart of preparing positive electrode material of lithium ion battery of the present invention;

[0029] Figure 2 This is a transmission electron microscope image of the lithium-ion battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0031] (1) Mixing a soluble metal salt, urea, and water to obtain a precursor solution; adding carbon cloth to the precursor solution to perform a hydrothermal reaction to obtain a carbon cloth loaded with metal oxides;

[0032] (2) placing the metal oxide-loaded carbon in a tubular furnace and heating it to a reaction temperature; after reaching the reaction temperature, atomizing the carbon source solution and passing it into the tubular furnace through a carrier gas, so that the carbon source and the metal oxide-loaded carbon cloth react at the reaction temperature; continuously passing the carbon source during the reaction; stopping passing the carbon source at the end of the reaction; and naturally cooling the carbon cloth to obtain the metal-coated carbon cloth loaded with carbon nanotubes;

[0033] (3) subjecting the carbon cloth loaded with carbon nanotubes and coated with metal to an oxidation reaction in an air atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with metal oxide;

[0034] (4) The carbon cloth loaded with carbon nanotubes and coated with metal oxides is mixed with a lithium source solution and subjected to a hydrothermal reaction to obtain a precursor; the precursor is calcined to obtain a positive electrode material for a lithium-ion battery.

[0035] In the present invention, the mass volume ratio of the soluble metal salt, urea and water in step (1) is preferably 1-20 g: 1-7 g: 50-80 mL, more preferably 2-17 g: 2-6 g: 57-72 mL, and more preferably 12 g: 3 g: 70 mL.

[0036] In the present invention, the soluble metal salt in step (1) is preferably one or more of cobalt nitrate, ferric nitrate, nickel nitrate, manganese nitrate, cobalt chloride, ferric chloride, nickel chloride, and ammonium vanadate, more preferably one or more of cobalt nitrate, ferric nitrate, manganese nitrate, cobalt chloride, and ammonium vanadate, and more preferably cobalt nitrate.

[0037] In the present invention, the step (1) further comprises immersing the carbon cloth in a precursor solution before the hydrothermal reaction; the immersion time is preferably 20 to 24 hours, more preferably 20, 21, 22, 23 or 24 hours, and more preferably 22 hours.

[0038] In the present invention, the temperature of the hydrothermal reaction in step (1) is preferably 120-130°C, more preferably 121-128°C, and more preferably 127°C; the time of the hydrothermal reaction is preferably 6-8h, more preferably 6, 6.5, 7, 7.5 or 8h, and more preferably 7.5h.

[0039] In the present invention, after the hydrothermal reaction in step (1), the step further includes washing with anhydrous ethanol and water in sequence, and then drying; the drying temperature is preferably 60-80°C, more preferably 63-77°C, and more preferably 67°C; the drying time is preferably 8-10h, more preferably 8, 8.5, 9, 9.5 or 10h, and more preferably 8.5h.

[0040] In the present invention, the carbon source solution in step (2) is preferably a mixed solution of anhydrous ethanol and water of the carbon source; the carbon source is preferably one or more of glucose, sucrose, water-soluble starch, dextrin, and citric acid, further preferably one or more of glucose, sucrose, and citric acid, and more preferably sucrose; the mass ratio of anhydrous ethanol to water is preferably 5-8:1, further preferably 6-8:1, and more preferably 7:1; the mass volume ratio of the mixed solution of soluble metal salt, carbon source, anhydrous ethanol and water is preferably 1-20 g:5-6 g:40-60 mL, further preferably 4-18 g:5.1-5.8 g:43-56 mL, and more preferably 11 g:5.4 g:51 mL.

[0041] In the present invention, the temperature for atomizing the carbon source solution in step (2) is preferably room temperature.

[0042] In the present invention, the carrier gas in step (2) is preferably argon; the flow rate of the carrier gas is preferably 5-50 mL / min, more preferably 18-42 mL / min, and more preferably 26 mL / min.

[0043] In the present invention, the reaction temperature in step (2) is preferably 900-1600°C, more preferably 970-1430°C, and more preferably 1280°C; the reaction time at the reaction temperature is preferably 10-120 min, more preferably 27-95 min, and more preferably 58 min; the heating rate is preferably 1-5°C / min, more preferably 1, 2, 2.5, 3, 4 or 5°C / min, and more preferably 3°C / min.

[0044] In the present invention, the temperature of the oxidation reaction in step (3) is preferably 200-500°C, more preferably 270-410°C, and more preferably 360°C; the time of the oxidation reaction is preferably 1-5h, more preferably 1, 2, 3, 4 or 5h, and more preferably 4h.

[0045] In the present invention, the concentration of the lithium source solution in step (4) is preferably 0.1-0.5 mol / L, more preferably 0.2-0.45 mol / L, and more preferably 0.33 mol / L; the mass volume ratio of the soluble metal salt to the lithium source solution is preferably 1-20 g:50-100 mL, more preferably 6-15 g:60-90 mL, and more preferably 14 g:80 mL.

[0046] In the present invention, the lithium source solution in step (4) is preferably an aqueous solution of a lithium source or an aqueous solution of a mixture of a lithium source and a phosphorus source; the lithium source is preferably one or more of lithium chloride, lithium hydroxide, lithium acetate, lithium citrate, and lithium dihydrogen phosphate, more preferably one or more of lithium hydroxide, lithium acetate, and lithium dihydrogen phosphate, and more preferably lithium hydroxide; the phosphorus source is preferably one or more of diammonium hydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid, more preferably one or more of diammonium hydrogen phosphate and lithium dihydrogen phosphate, and more preferably diammonium hydrogen phosphate; the molar ratio of lithium element to phosphorus element in the aqueous solution of a mixture of the lithium source and the phosphorus source is preferably 1:1.

[0047] In the present invention, the temperature of the hydrothermal reaction in step (4) is preferably 200-250° C., more preferably 210-240° C., and more preferably 230° C.; the time of the hydrothermal reaction is preferably 2-20 h, more preferably 4-17 h, and more preferably 13 h.

[0048] In the present invention, the calcination temperature in step (4) is preferably 700-1500°C, more preferably 780-1410°C, and more preferably 1320°C; the calcination time is preferably 2-12h, more preferably 3-8h, and more preferably 7h.

[0049] The present invention also provides a lithium ion battery positive electrode material prepared by the above preparation method.

[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0051] This embodiment provides a LiCoO2@CNT / CC positive electrode material, and its preparation process is as follows: Figure 1 As shown, the following steps are included:

[0052] (1) 1.5 g Co(NO3)2•6H2O and 1 g urea were dissolved in 60 mL ultrapure water to obtain a precursor solution. Carbon cloth (CC, 1.5 cm × 1.5 cm) was immersed in the precursor solution for 24 h, and then transferred together into a stainless steel-lined autoclave and kept at 120 °C for 6 h. After cooling to room temperature, it was washed with anhydrous ethanol and ultrapure water in turn, and then dried at 80 °C for 10 h to obtain carbon cloth loaded with Co3O4 nanoparticles (Co3O4 / CC).

[0053] (2) Place Co3O4 / CC in a tube furnace and heat the tube furnace to 900°C at 3°C / min; then dissolve 5g of glucose in a mixed solution of 50mL of water and anhydrous ethanol (the mass ratio of anhydrous ethanol to water is 5:1), atomize at room temperature and then load it into the tube furnace with argon gas (the flow rate of argon gas is 10mL / min); keep the tube furnace at 900°C for 90min, stop introducing the carbon source at the end of the insulation, and naturally cool to room temperature to obtain carbon cloth loaded with carbon nanotubes coated with cobalt (Co@CNT / CC);

[0054] (3) The Co@CNT / CC was oxidized in a muffle furnace at 350 °C for 3 h to obtain a carbon cloth loaded with carbon nanotubes and coated with Co3O4 (Co3O4@CNT / CC);

[0055] (4) Place Co3O4@CNT / CC in 50 mL of lithium hydroxide solution (Li +The concentration is 0.2 mol / L), and then placed in an autoclave, kept at 200 ° C hydrothermal conditions for 12 hours, cooled naturally, washed with anhydrous ethanol and ultrapure water in turn, and then dried at 80 ° C for 10 hours, and then placed in a tube furnace and calcined at 800 ° C for 4 hours under a protective atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with lithium cobalt oxide (LiCoO2@CNT / CC); that is, a positive electrode material for lithium ion batteries, and its transmission electron microscopy test results are as follows Figure 2 shown.

[0056] The battery performance test of LiCoO2@CNT / CC positive electrode material uses CR2025 button cells. The negative electrode uses metal lithium sheet, and the electrolyte uses 1 mol / L LiPF6 / EC:DMC (1:1). The assembled battery is assembled in a glove box filled with an inert atmosphere, and the assembled battery is tested for charge and discharge performance using a blue battery test system. Under the condition of a charge and discharge rate of 1C, the initial discharge capacity of the positive electrode material reaches 126.5mAh / g, and the capacity retention rate after 50 cycles is 94.3%. Example 2

[0057] This embodiment provides a LiNi a Co b Mn c O2@CNT / CC cathode material, its preparation process is as follows Figure 1 As shown, the following steps are included:

[0058] (1) 5.8 g Co(NO3)2•6H2O, 5.8 g Ni(NO3)2•6H2O, 5.7 g Mn(NO3)2•6H2O and 1 g urea were dissolved in 70 mL ultrapure water in a molar ratio of Co:Ni:Mn=1:1:1 to obtain a precursor solution. A carbon cloth (CC, 1.5 cm × 1.5 cm) was immersed in the precursor solution for 22 h and then transferred to a stainless steel-lined autoclave and kept at 125 °C for 6.5 h. After cooling to room temperature, the carbon cloth was washed with anhydrous ethanol and ultrapure water in turn and then dried at 70 °C for 10 h to obtain a carbon cloth loaded with nickel-cobalt-manganese trimetallic hydroxide nanoparticles (NiCC). a Co b Mn c (OH)3 / CC);

[0059] (2) Ni a Co b Mn c(OH)3 / CC was placed in a tube furnace, and the temperature of the tube furnace was raised to 900℃ at 3℃ / min; 5g of glucose was dissolved in a mixed solution of 50mL of water and anhydrous ethanol (the mass ratio of anhydrous ethanol to water was 8:1), and then atomized at room temperature and loaded into the tube furnace with argon gas (the flow rate of argon gas was 20mL / min); the tube furnace was kept at 900℃ for 120min, and the carbon source was stopped at the end of the heat preservation, and it was naturally cooled to room temperature to obtain a carbon cloth loaded with carbon nanotubes coated with nickel, cobalt and manganese trimetallic (Ni a Co b Mn c @CNT / CC);

[0060] (3) Ni a Co b Mn c @CNT / CC was oxidized in a muffle furnace at 200 °C for 6 h to obtain a carbon cloth loaded with carbon nanotubes and coated with nickel, cobalt and manganese trimetallic oxides (Ni a Co b Mn c O@CNT / CC);

[0061] (4) Ni a Co b Mn c O@CNT / CC was placed in 50 mL of lithium hydroxide solution (Li + The mixture was placed in an autoclave and kept at 200 °C for 12 h. After cooling naturally, it was washed with anhydrous ethanol and ultrapure water in turn. It was then dried at 60 °C for 8 h. It was then placed in a tube furnace and calcined at 800 °C for 2 h under a protective atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with lithium nickel cobalt manganese oxide (LiNi a Co b Mn c O2@CNT / CC); that is, the positive electrode material of lithium-ion batteries.

[0062] LiNi a Co b Mn c The O2@CNT / CC positive electrode material was assembled into a battery according to the method of Example 1. After testing, the initial discharge capacity of the positive electrode material reached 136.5 mAh / g, and the capacity retention rate after 50 cycles was 97.6%. Example 3

[0063] This embodiment provides a LiFePO4@CNT / CC positive electrode material, and its preparation process is as follows: Figure 1 As shown, the following steps are included:

[0064] (1) 1.5 g Fe(NO3)3•9H2O and 1 g urea were dissolved in 60 mL ultrapure water to obtain a precursor solution. Carbon cloth (CC, 1.5 cm × 1.5 cm) was immersed in the precursor solution for 24 h, and then transferred together into a stainless steel-lined autoclave and kept at 120 °C for 7 h; after cooling to room temperature, it was washed with anhydrous ethanol and ultrapure water in turn, and then dried at 60 °C for 9 h to obtain carbon cloth loaded with Fe2O3 nanoparticles (Fe2O3 / CC);

[0065] (2) Fe2O3 / CC was placed in a tube furnace, and the temperature of the tube furnace was raised to 1000°C at 5°C / min; 5 g of sucrose was dissolved in a mixed solution of 50 mL of water and anhydrous ethanol (the mass ratio of anhydrous ethanol to water was 8:1), and then atomized at room temperature and loaded into the tube furnace with argon gas (the flow rate of argon gas was 30 mL / min); the tube furnace was kept at 1000°C for 100 min, and the carbon source was stopped at the end of the insulation, and the mixture was naturally cooled to room temperature to obtain carbon cloth loaded with carbon nanotubes and coated with iron (Fe@CNT / CC);

[0066] (3) Fe@CNT / CC was oxidized in a muffle furnace at 200 °C for 5 h to obtain carbon cloth loaded with carbon nanotubes and coated with Fe2O3 (Fe2O3@CNT / CC);

[0067] (4) Fe2O3@CNT / CC was placed in a 50 mL mixed solution of lithium acetate and ammonium dihydrogen phosphate (Li + The mixture was prepared by mixing the obtained carbon cloth with carbon nanotubes and lithium iron phosphate (LiFePO4@CNT / CC) in a tubular furnace and keeping it warm at 220 °C for 12 h. The mixture was naturally cooled and washed with anhydrous ethanol and ultrapure water in turn. The mixture was then dried at 80 °C for 9 h. The mixture was then placed in a tubular furnace and calcined at 800 °C for 4 h under a protective atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with lithium iron phosphate (LiFePO4@CNT / CC), which is a positive electrode material for lithium ion batteries.

[0068] The LiFePO4@CNT / CC positive electrode material was assembled into a battery according to the method of Example 1. After testing, the initial discharge capacity of the positive electrode material reached 148.2 mAh / g, and the capacity retention rate after 50 cycles was 99.6%. Comparative Example 1

[0069] This comparative example provides a LiCoO2 / CC positive electrode material, which is specifically referred to Example 1, except that the carbon nanotubes are not coated, that is, step (2) and step (3) of Example 1 are not performed.

[0070] The LiCoO2 / CC positive electrode material was assembled into a battery according to the method of Example 1. After testing, the initial discharge capacity of the positive electrode material reached 106.2 mAh / g, and the capacity retention rate after 50 cycles was 79.8%.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: The following steps are involved: (1) mixing a soluble metal salt, urea, and water to obtain a precursor solution; Adding carbon cloth to a precursor solution and performing a hydrothermal reaction to obtain a carbon cloth loaded with metal oxides; (2) placing the metal oxide-loaded carbon in a tubular furnace and heating it to a reaction temperature, atomizing the carbon source solution after reaching the reaction temperature and then passing the solution into the tubular furnace through a carrier gas, so that the carbon source and the metal oxide-loaded carbon cloth react at the reaction temperature, continuously passing the carbon source during the reaction, stopping passing the carbon source at the end of the reaction, and naturally cooling the solution to obtain a carbon cloth loaded with carbon nanotubes and coated with metal; (3) subjecting the carbon cloth loaded with carbon nanotubes and coated with metal to an oxidation reaction in an air atmosphere to obtain a carbon cloth loaded with carbon nanotubes and coated with metal oxide; (4) mixing the carbon cloth loaded with carbon nanotubes and coated with metal oxide with a lithium source solution and subjecting the mixture to a hydrothermal reaction to obtain a precursor; and calcining the precursor to obtain a positive electrode material for a lithium-ion battery.

2. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: In the step (1), the mass volume ratio of the soluble metal salt, urea and water is 1-20 g: 1-7 g: 50-80 mL.

3. The method for preparing a positive electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The soluble metal salt in step (1) is one or more of cobalt nitrate, ferric nitrate, nickel nitrate, manganese nitrate, cobalt chloride, ferric chloride, nickel chloride and ammonium vanadate.

4. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, characterized in that: The step (1) also includes immersing the carbon cloth in the precursor solution for 20 to 24 hours before the hydrothermal reaction is carried out; the temperature of the hydrothermal reaction is 120 to 130° C.; and the time of the hydrothermal reaction is 6 to 8 hours.

5. The method for preparing a positive electrode material for a lithium ion battery according to claim 1, 2 or 4, characterized in that: The carbon source solution in step (2) is a mixed solution of anhydrous ethanol and water as the carbon source; the carbon source is one or more of glucose, sucrose, water-soluble starch, dextrin, and citric acid; the mass volume ratio of the mixed solution of soluble metal salt, carbon source, anhydrous ethanol and water is 1-20g:5-6g:40-60mL.

6. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: In the step (2), the carrier gas is argon; the flow rate of the carrier gas is 5 to 50 mL / min; the reaction temperature is 900 to 1600° C.; and the reaction time at the reaction temperature is 10 to 120 min.

7. The method for preparing a positive electrode material for a lithium ion battery according to claim 1 or 6, characterized in that: The temperature of the oxidation reaction in step (3) is 200 to 500° C.; the time of the oxidation reaction is 1 to 5 hours.

8. The method for preparing a positive electrode material for a lithium ion battery according to claim 7, characterized in that: The concentration of the lithium source solution in step (4) is 0.1-0.5 mol / L; the mass volume ratio of the soluble metal salt to the lithium source solution is 1-20 g: 50-100 mL; The lithium source solution is an aqueous solution of a lithium source or an aqueous solution of a mixture of a lithium source and a phosphorus source; the lithium source is one or more of lithium chloride, lithium hydroxide, lithium acetate, lithium citrate, and lithium dihydrogen phosphate; the phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid; The molar ratio of lithium element to phosphorus element in the aqueous solution of the lithium source and the phosphorus source mixture is 1:

1.

9. The method for preparing a positive electrode material for a lithium ion battery according to claim 8, characterized in that: In the step (4), the temperature of the hydrothermal reaction is 200-250° C.; the time of the hydrothermal reaction is 2-20 hours; the temperature of the calcination is 700-1500° C.; and the time of the calcination is 2-12 hours.

10. A lithium ion battery positive electrode material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Manufacturing method of carbon coated modified lithium cobaltate anode material

    CN102931397A

  • Method for preparing carbon-coating nickel cobalt lithium manganate anode material

    CN108155360A

  • Method for preparing carbon nanotube array supported lithium titanate flexible electrode material

    CN110299516A

  • Carbon-coated lithium titanate electrode material and preparation method thereof

    CN113437269A